ALAT PENDETEKSI KERUSAKAN CELL ACCU - Fahmi, Ahmad Fahrizal; Arsana, I Made (Universitas Negeri Surabaya, 2021)
The battery cell damage detection tool solves the problem of using a wet type battery (lead acid), most battery services analyze cell damage by cutting the battery cover with the awakening of this tool analyzing battery cell damage without having to cut the battery cover and detecting each cell so that it saves processing time checking the battery and analyzing the damage. This type of design is in the form of an experimental engineering method that aims to determine the damage to the battery cells and the interconnections between cells. The results of this experiment aim to shorten the time and effort when sorting used batteries quickly and without damaging the battery cover